Population structure leads to male‐biased population sex ratios under environmental sex determination. (12th December 2018) - Butka, Emily G.; Freedberg, Steven
Abstract: Spatial structure has been shown to favor female‐biased sex allocation, but current theory fails to explain male biases seen in many taxa, particularly those with environmental sex determination (ESD). We present a theory and accompanying individual‐based simulation model that demonstrates how population structure leads to male‐biased population sex ratios under ESD. Our simulations agree with earlier work showing that the high productivity of female‐producing habitats creates a net influx of sex‐determining alleles into male‐producing habitats, causing larger sex ratio biases, and lower productivity in male‐producing environments (Harts et al. 2014). In contrast to previous findings, we show that male‐biasing habitats disproportionately impact the global sex ratio, resulting in stable male‐biased population sex ratios under ESD. The failure to detect a male bias in earlier work can be attributed to small subpopulation sizes leading to local mate competition, a condition unlikely to be met in most ESD systems. Simulations revealed that consistent male biases are expected over a wide range of population structures, environmental conditions, and genetic architectures of sex determination, with male excesses as large as 30 percent under some conditions. Given the ubiquity of genetic structure in natural populations, we predict that modest, enduring male biased allocation should be common in ESD species, a pattern consistent with reviews of ESD sex ratios.